Pet Service Information System Using the Rational Unified Process Method: Case Study on One of The Pet Shop in Bandung - Dzakiyyah, Anisa Rahma; Irawan, Debi; Abdurahman, Fikri Irawan; Solihin, Solihin; Ramlan, Isak (LPPM STMIK Mardira Indonesia, 2023)
Pet ownership is prevalent in the present period, and Pet Shops are enterprises that have arisen in conjunction with this phenomenon. One of The Pet Shop in Bandung is a small to medium-sized firm that caters to pet aficionados by offering a wide range of pet goods, including food and grooming services. One of The Pet Shop in Bandung has faced various obstacles in its business operations, such as inadequate documentation of item availability and insufficient product information provided to clients. In order to tackle these difficulties, the researcher utilized the Rational Unified Process (RUP) methodology to construct a website for One of The Pet Shop in Bandung. The RUP technique is appropriate for this research because it incorporates user perspectives throughout every stage. The website underwent Usability Testing with five user responders utilizing the System Usability Scale questionnaire. The questionnaire assessment utilizing the Likert scale and Usability measurement yielded a score of 72%, signifying its appropriateness.